Studies on propagation of vibroacoustic energy and its influence on structure vibration in a large-size object - DĄBROWSKI, Zbigniew; DZIURDŹ, Jacek; KLEKOT, Grzegorz (Archives of Acoustics, 2007)
Large-size spaces of general use are usually characterized by atypical acoustic features. The Great Lecture Hall of Warsaw Technical University can be an example, as its maximum crosswise dimension is comparable with its height. When powerful amplification equipment is used for special events, the question that arises is possible negative influence of acoustic signal energy on the building’s structure, especially the skylight. The paper presents selected results of studies on acoustically induced vibrations of construction elements and tries to answer the above formulated question.